Dissection of loci conferring resistance to stripe rust in Chinese wheat landraces from the middle and lower reaches of the Yangtze River via genome-wide association study. (October 2019) - Cheng, Yukun; Li, Jian; Yao, Fangjie; Long, Li; Wang, Yuqi; Wu, Yu; Li, Jing; Ye, Xueling; Wang, Jirui; Jiang, Qiantao; Kang, Houyang; Li, Wei; et al.
Highlights: Chinese wheat landraces were assessed for stripe rust resistance at the adult-plant stage. Performed a genome-wide association study to APR stripe rust using DArT array and SSR markers. Identified eight potential novel APR loci for wheat stripe rust. Haplotype analysis revealed that accessions carrying APR loci showed enhanced degrees of resistance. Abstract: Stripe rust ( Yr ), caused by the fungal pathogen Puccinia striiformis f. sp. tritici, is a devastating foliar disease of wheat in China. Chinese wheat landraces originating from the middle and lower reaches of the Yangtze River are potential stripe-rust resistance resources. To identify APR genes for stripe-rust resistance, a panel of 188 accessions derived from the middle and lower reaches of the Yangtze River were inoculated with a mixture of Chinese P. striiformis f. sp . tritici races and resistance evaluated under field conditions in five environments at adult-plant stages. Seventy-three accessions showed degrees of stable resistance. Combining phenotypic datasets from multiple field experiments with high-quality Diversity Arrays Technology and simple sequence repeat markers, we detected 21 marker-trait associations spanning 18 quantitative trait loci (QTLs) on chromosomes 1B, 2A, 2B, 3B, 4A, 5A, 5B, 6B, and 6D, respectively. Single QTLs explained 9.67% to 16.14% of the observed phenotypic variation. Nine QTLs co-localized with previously reported Yr genes or genomic regions. The remaining QTLs were potential novel loci associated with adult-stage stripe-rust resistance. Two novel QTLs, QYr.sicau-3B.2 and QYr.sicau-5B.3, located on chromosomes 3B and 5B significantly explained 16.14% and 11.16% of the phenotypic variation, respectively. Haplotype analysis revealed that accessions carrying APR variants or their combinations showed enhanced degrees of resistance. The potentially novel loci or genomic regions associated with adult-stage resistance may be useful to improve stripe-rust resistance in current wheat cultivars and for future isolation of stripe-rust resistance genes.